Revisão taxonômica do gênero Cholomyia Bigot,1884 (Diptera, Tachinidae, Myiophasiini) - Santis, Marcelo Domingos de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The genus Cholomyia Bigot, 1884 belongs to the tribe Myiophasiini (Diptera, Tachinidae, Tachininae) and presents Neotropical and Nearctic distribution. The most notable feature of this genus is the elongate median legs in males. There are four species described in the genus: C. acromion (Wiedemann, 1824), C. filipes (Walker, 1857), and C. inaequipes Bigot, 1884. C. calceata (Wulp, 1891). In this work, a taxonomic revision is made from materials deposited in national and international scientific collections. All species have been recognized and studied except C. Calceata (Wulp, 1891), because no material was examined and the available data are restricted to the original description. A new species is described and proposed to Costa Rica. An identification key to the species studied was made. The first description of male terminalia to genus is performed in this work. New distributional data are added to the species

O gênero Cholomyia Bigot, 1884 pertence à tribo Myiophasiini (Diptera, Tachinidae, Tachininae) e tem distribuição Neotropical e Neártica. A presença de perna mediana alongada em machos é a característica mais notável desse gênero. Existem quatro espécies descritas no gênero: C. acromion (Wiedemann, 1824), C. filipes (Walker, 1857), C. inaequipes Bigot, 1884 e C. calceata (Wulp, 1891). No presente trabalho, uma revisão taxonômica é realizada a partir de materiais depositados em coleções científicas nacionais e internacionais. Todas as espécies foram reconhecidas e estudadas, exceto C. Calceata (Wulp, 1891) pois nenhum material foi encontrado e os dados disponíveis estão restritos à descrição original. Uma nova espécie é proposta e descrita para a Costa Rica. Foi elaborada uma chave de identificação para as espécies estudadas. A primeira descrição das terminálias masculinas para o gênero é realizada nesse trabalho. Novos dados distribucionais são adicionados às espécies
Keywords: Diptero - Distribuição geográfica; Tachinidae; Taxonomia numerica; Inseto - Morfologia; Diptera - Geographical distribution